(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
A well-recognized technique for producing compressive residual stresses beneath the surface of metal is laser shock peening (LSP), which increases the material's durability to wear and corrosion and improves fatigue life. Comparing LSP to traditional mechanical shot peening, it provides a more dependable surface treatment and may minimize microstructural damage. This surface treatment method involves directing a powerful laser pulsation at the superficial in extremely tiny pauses. Due to the capabilities available in this alloy AA7075-T651. As an important formability, automation and corrosion resistance, it will certainly have very large uses, including aircraft structures, and to improve the properties of this alloy, this technical method was used. The treated surface of Al-alloy 7075-T651 was made harder and more desirable during this investigation by employing a novel approach that involved the use of pure water and hydrofluoric acid (HF) as confinement layers. It was found that applying Hydrofluoric Acid (HF) significantly extended the pieces' fatigue life after laser peening as compared to unpeened specimens and pure water. Additionally, the Vickers hardness test results revealed that LSP with the utilized two confinement liquid, as well as unpeened samples, exhibited hardness values of 153HV30, 121HV30, and 94HV30, respectively, demonstrating a substantial improvement in hardness properties. The test results show that, when compared to unpeened samples, every site of interest deal with the in-elevation cycle fatigue zone by LSP with two confinement liquid achieved a considerable improvement in life and strength, arriving at 88%and 72%, respectively. The SEM images showed that the untreated specimens had surface crack initiation location. The peened specimens showed two regions, the hardened and non-hardened region. The depth of the hardened area of the peened specimens was measured. The results of the experiment support the assumption that peening increases the fatigue life of alloys. The hardened surface and compressive residual stress field created by peening make it harder for cracks to initiate and propagate.